PERAN PEMAHAMAN AMANAT AGUNG TERHADAP KEPEDULIAN PENGINJILAN PRIBADI DI PEMUDA GEREJA BETHEL INDONESIA BRIDE OF CHRIST BATAM - Gomgom Purba; Roy Gabe Marpaung (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2024)
The purpose of this research is to find out how the understanding of the Great Commission plays a role in caring for personal evangelism in the youth of Bethel Indonesia Bride Of Christ Church Batam so that the Youth of Bethel Indonesia Church Bride Of Christ Batam have the enthusiasm and courage to carry out personal evangelism as part of the Great Commission. This research is descriptive qualitative research and the resource persons in this research are the Bethel Indonesia Bride Of Christ Batam Church youth who were taken randomly. Research data was collected through in-depth interviews using the coding method. The data obtained was then analyzed using the stages of condensation, data display, drawing conclusions. The research results show that understanding the Great Commission plays a role in caring for personal evangelism in the Bethel Indonesia Bride of Christ Batam Church Youth, which is a natural expression of living Christianity. Jesus Christ is the pioneer of mission itself. God's plan in His eternal sending is to bring transformation and liberation to humans and all of His creation to bring about the eternal kingdom of God. Personal evangelism is an attempt to bring about a breakthrough in the boundaries between faith in Jesus Christ and the absence of it. The form of personal evangelism concern at Bethel Indonesia Bride Of Christ Batam Church Youth is carrying out direct personal evangelism or face to face, via WhatsApp and intensely calling people who are in the process of evangelism. This fact is also supported by the statement of the Bethel Indonesia Bride Of Christ Batam Church Youth who felt a deep bond between themselves and the church and the people who were the targets of personal evangelism.